The effect of temperature and other factors on plastics and elastomers - McKeen, Laurence W. (William Andrew, 2023)
The Effect of Temperature and Other Factors on the Properties of Plastics and Elastomers, Fourth Edition provides data on the wide spectrum of plastics and TPEs with special reference to thermal stability. The mechanical, physical and electrical properties of plastics and elastomers are described as a function of temperature and humidity to help with the design of lighter more cost-effective plastic parts to replace metal ones. In this new edition, expertly edited data makes it easy for readers to learn about the properties of plastic materials without having to search the general literature or depend on suppliers. Additional types of plastics are examined, and the latest data on material characteristics are provided. Complex details such as how the thermal prehistory can effect final mechanical properties, and how temperature scans reveal dynamic mechanical behavior are also examined to build a deeper understanding of the materials.
Previous edition: 2014.
Keywords: Plastics -- Thermal properties.; Plastics -- Testing.; Elastomers -- Thermal properties.; Elastomers -- Testing.; elektronické knihy; electronic books